ANALYSIS OF PRODUCTION EFFICIENCY AND INCOME OF IRRIGATED RICE (ORYZA SATIVA L) FARMING IN BANDAR BARU DISTRICT, PIDIE JAYA REGENCY - Maidawati; Adhiana; Mawardati (CV. Radja Publika, 2023)
This study aims to analyze the production efficiency and income of lowland rice (Oryza sativa L.) farming in Bandar Baru District, Pidie Jaya Regency. The study was conducted in June–July 2023 with 80 respondents. Data were obtained through interviews and questionnaires, and analyzed using stochastic frontier analysis (SFA) and dual cost functions. The results indicate that lowland rice farming has achieved technical efficiency, but is not yet allocatively or economically efficient. As a result, farmer income is not optimal, although it still has the potential to be increased through improved production input management.